Chronic Bullous Disease of Childhood: A Case Report and Review of Literature of Bullous Diseases in Children - Pradhan, Susmita; Jha, Krishna; Kumari, Priyanka; Shrestha, Shristi; Jha, Anil Kumar (Nepal Journal of Dermatology, Venereology & Leprology, 2022)
We describe a case of a 5-year-old boy who presented with multiple mild itchy and painful blisters predominantly over his trunk and limbs for one year with multiple tense bullae with hypopyon signs resulting in a half-and-half appearance of the blisters. A skin biopsy showed subepidermal separation with predominantly neutrophils and eosinophils in the bulla cavity and mixed infiltrate in the papillary dermis. We would like to report a case of chronic bullous disease of childhood and review its differentials for diagnostic approaches to blistering disease in children.